2013
DOI: 10.1371/journal.pone.0072949
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cost Saving of Epoetin alfa in Elective Hip or Knee Surgery due to Reduction in Blood Transfusions and Their Side Effects: A Discrete-Event Simulation Model

Abstract: ObjectivesTransfusion of allogeneic blood is still common in orthopedic surgery. This analysis evaluates from the perspective of a German hospital the potential cost savings of Epoetin alfa (EPO) compared to predonated autologous blood transfusions or to a nobloodconservationstrategy (allogeneic blood transfusion strategy)during elective hip and knee replacement surgery.MethodsIndividual patients (N = 50,000) were simulated based on data from controlled trials, the German DRG institute (InEK) and various publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
(63 reference statements)
0
17
1
1
Order By: Relevance
“…Nevertheless, and in spite of the differences between both studies, in ours, we did not detect any supplementary benefit in RBC transfusion reduction, in the subgroups of intracapsular HF, or in those patients with highest Hb levels (in our case those with inclusion Hb level ≥ 115 g/L). Data from our study also contrast with the established benefit of preoperative EPO and IV iron in patients undergoing elective major orthopedic procedures . Nevertheless, results obtained in the previous trials are difficult to extrapolate to patients with HF.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, and in spite of the differences between both studies, in ours, we did not detect any supplementary benefit in RBC transfusion reduction, in the subgroups of intracapsular HF, or in those patients with highest Hb levels (in our case those with inclusion Hb level ≥ 115 g/L). Data from our study also contrast with the established benefit of preoperative EPO and IV iron in patients undergoing elective major orthopedic procedures . Nevertheless, results obtained in the previous trials are difficult to extrapolate to patients with HF.…”
Section: Discussioncontrasting
confidence: 89%
“…[25][26][27][28][29] Additionally, the benefits of perioperative use of erythropoietin (EPO) with or without IV iron in major orthopedic procedures are well established. [30][31][32][33][34][35][36][37][38][39][40][41] This evidence could be promising for patients with HF. We hypothesized if the sum up of EPO with the concomitant use of FCM could serve to save blood transfusions in patients with HF.…”
mentioning
confidence: 99%
“…A recent study using computer modelling, demonstrated the cost effectiveness of erythropoeitin therapy over ABT if initiated at preoperative haemoglobin between 100 and 130 g/L. 24 Other factors, presumed or known to be associated with the use of ABT, such as revision surgery, duration, age, gender, hip versus knee arthroplasty and use of anticoagulants or antiplatelet agents, 25 were not significantly associated with ABT utilization in our cohort. Although the ratio of hip/knee surgery was reversed in CKD patients compared with controls, there was no difference in the use of ABT between those having hip or knee replacement.…”
Section: Discussionmentioning
confidence: 57%
“…While this was not explored in the present study, we could anticipate that even if low‐normal haemoglobin levels are tackled by strategies that have been shown to be effective in patients with CKD, including preoperative intravenous iron with or without erythropoietin, the use of ABT in this cohort would be reduced. A recent study using computer modelling, demonstrated the cost effectiveness of erythropoeitin therapy over ABT if initiated at preoperative haemoglobin between 100 and 130 g/L …”
Section: Discussionmentioning
confidence: 99%
“…La stratégie d'administration d'Epo est largement préférée à la transfusion autologue, et serait efficiente par rapport à une stratégie de transfusion conventionnelle [22,23]. Le problème est que les différentes stratégies sont en général comparées deux à deux, et qu'il est difficile de savoir si, pour une chirurgie programmée, l'administration d'Epo est préférable à l'utilisation des seuils transfusionnel ou le monitoring de l'Hb par exemple.…”
unclassified